Afibercept treatment for macular edema with and without serous retinal detachment due to branch retinal vein occlusion - Irgat,Saadet Gültekin (2022)
ABSTRACT Purpose: To evaluate the effectiveness of intravitreal aflibercept treatment for macular edema with and without serous retinal detachment due to branch retinal vein occlusion. Methods: Thirty-seven eyes with branch retinal vein occlusion treated with intravitreal aflibercept injection for macular edema were evaluated retrospectively. The patients were divided into two groups according to whether they showed serous retinal detachment on spectral domain optical coherence tomography. Pro re nata regimen was applied after 1 dose of intravitreal aflibercept injection. After the initial injection, control treatments were administered at months 1, 2, 3, 6, and 12. The best-corrected visual acuity and central macular thickness were measured. Results: Fifteen patients had serous retinal detachment, and 22 with macular edema only (non-serous retinal detachment). The central macular thickness was significantly greater in the group with than in the group without serous retinal detachment (811.73 ± 220.68 µm and 667.90 ± 220.68 µm, respectively, p=0.04). The difference between the groups disappeared from the third month. The central macular thickness was similar between the two groups at the last control treatment (407.27 ± 99.08 µm and 376.66 ± 74.71 µm, p=0.66). The best-corrected visual acuity increased significantly in both groups. No significant difference was found between the two groups in terms of the best-corrected visual acuities at baseline and the final control. Conclusion: The intravitreal aflibercept treatment was highly effective in improving best-corrected visual acuity and central macular thickness in patients with branch retinal vein occlusion-induced macular edema independent of serous retinal detachment.